2023
DOI: 10.1371/journal.pntd.0010706
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and antimicrobial resistance pattern of E. coli O157:H7 isolated from foods of Bovine origin in Dessie and Kombolcha towns, Ethiopia

Abstract: E. coli are frequently isolated food-borne pathogens from meat, milk, and their products. Moreover, there has been a significant rise in the antimicrobial resistance patterns of E. coli O157:H7 to commonly used antibiotics. A cross-sectional study was conducted from October 2019 to July 2021 to estimate prevalence and identify associated factors of E. coli and E. coli O157:H7 and to determine antibiotic resistance pattern of E. coli O157:H7 from foods of bovine origin in Dessie and Kombolcha towns. A total of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 80 publications
0
5
1
Order By: Relevance
“…In addition, the survival of E. coli on manure‐amended agricultural farms could be affected by the soil management system of the farm (Franz et al., 2005 ). In this study, no E. coli O157:H7 was detected, but previous studies reported E. coli O157:H7 in foods of animal origin in Ethiopia (Abebe et al., 2023 ; Hamid et al., 2018 ). The common source of contamination of food of animal origin with E. coli O157:H7 is the fresh feces of cattle (Ferens & Hovde, 2010 ).…”
Section: Discussioncontrasting
confidence: 68%
“…In addition, the survival of E. coli on manure‐amended agricultural farms could be affected by the soil management system of the farm (Franz et al., 2005 ). In this study, no E. coli O157:H7 was detected, but previous studies reported E. coli O157:H7 in foods of animal origin in Ethiopia (Abebe et al., 2023 ; Hamid et al., 2018 ). The common source of contamination of food of animal origin with E. coli O157:H7 is the fresh feces of cattle (Ferens & Hovde, 2010 ).…”
Section: Discussioncontrasting
confidence: 68%
“…While Senbetu ( 2014 ) and Habtamu et al ( 2018 ) from Hawassa reported a higher prevalence rate of S. enterica , 25%, and 17.8%, respectively. Among the S.enterica prevalence reports from the Amhara region, Abebe et al ( 2023 ) (Dessie and Kombolcha), Mulaw ( 2017 ), and Hailu et al ( 2015 ) (Gondor) reported 5.92%, 9.35%, and 3.24%, respectively, which is lower than the S.enterica prevalence report during the wet season.…”
Section: Discussionmentioning
confidence: 77%
“…Contamination of human milk consumption is one of the biggest concerns worldwide because of the presence of microbial and antibiotic residues in milk [5]. Milk may contain contaminants, such as pathogenic bacteria such as Listeria monocytogenes, Salmonella spp., Escherichia coli, and Staphylococcus aureus, as well as residues of antibiotics, pesticides, and other chemicals, which can be harmful to human health [6]. Penicillin, tetracycline, sulfonamides, cephalosporins, and streptomycin, which can be a risk to human health due to the development of antibiotic resistance [7], are the main antibiotics found in milk.…”
Section: Introductionmentioning
confidence: 99%
“…Penicillin, tetracycline, sulfonamides, cephalosporins, and streptomycin, which can be a risk to human health due to the development of antibiotic resistance [7], are the main antibiotics found in milk. Residues and contaminants in dairy products for final consumption have previously been reported in other countries [6][7][8][9][10][11][12][13]. The National Institute for Food and Drug Surveillance (INVIMA) of the Colombian Government regulates and controls drugs and other food contaminants in Colombia.…”
Section: Introductionmentioning
confidence: 99%